Relationship of Socio-economic Profile of the Turmeric Growing Farmers to their Training Need - Kumar, Anil; Paswan , A.K.; Ansari, M. N.; Singh, A. K. (Indian Journal of Extension Education, 2016)
A study on training needs of turmeric growers in Samastipur and Muzaffarpur district of Bihar was undertaken. The  findings revealed that majority of turmeric growers belong to the advance age group, literate, possessing small size of land  holding, low income group. The maximum per cent age of respondents has medium economic motivation, crop intensity  and level of knowledge. The results revealed that training need in plant protection measure was given top priority. The  other important areas of cultivation in which turmeric growers have shown their desire were high yielding variety,  fungicidal seed treatment, sowing method, sowing time and fertilizer management. The most important factors  influencing the training needs of turmeric growers in relation to turmeric production were cropping intensity, economic  motivation and knowledge which were found to be positively and significantly associated with the training need of  turmeric growers. These factors should be kept in view while formulating any training programme. The other independent  variables such as family education, size of land holding and area under turmeric cultivation were not able to create such  positive correlation as in the case of other selected independent variables.
Keywords: Characteristic profile; training needs, turmeric; growers